New exact solutions of the Dirac equation. IX; Soviet Physics Journal; Vol. 21, iss. 3 - Bagrov V. G. Vladislav Gavriilovich; Gitman D. M.; Zadorozhnyi V. N. Valery Nikolaevich; Shapovalov A. V. Aleksandr Vasilyevich; Shapovalov V. N. (1978, 1978)
Title screen